(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
ekuookn vaxzsth Hkk"kk dsßáweSfuTeÞ (Humanism) dk fgUnh :ikUrjgSA1 áweSfuTe ’kCn dh mRifr ySfVuHkk"kk áwEul* ls gqbZ gSA bl izdkj ^áweu* ’kCn esa ^bTe* izR;; yxus lsßáweSfuTeÞ vFkkZr ekuookn ’kCn dh mRifr gqbZA